Differential Relationships among Circulating Inflammatory and Immune Activation Biomediators and Impact of Aging and Human Immunodeficiency Virus Infection in a Cohort of Injection Drug Users - Kirk, Gregory D.; Dandorf, Stewart; Li, Huifen; Chen, Yiyin; Mehta, Shruti H.; Piggott, Damani A.; Margolick, Joseph B.; Leng, Sean X. (Frontiers in Immunology, 2017)
As individuals with human immunodeficiency virus (HIV) infection live longer, aging and age-related chronic conditions have become major health concerns for this vulnerable population. Substantial evidence suggests that chronic inflammation and immune activation contribute significantly to chronic conditions in people aging with or without HIV infection. As a result, increasing numbers of inflammation and immune activation biomediators have been measured. While very few studies describe their in vivo relationships, such studies can serve as an important and necessary initial step towards delineating the complex network of chronic inflammation and immune activation. In this study, we evaluated in vivo relationships between serum levels of neopterin, a biomediator of immune activation, and 4 commonly described inflammatory biomediators: soluble tumor necrosis factor (TNF)-alpha receptor (sTNFR)-1, sTNFR-2, interleukin (IL)-6, and C-reactive protein (CRP), as well as the impact of HIV infection and aging in the AIDS Linked to the Intravenous Experience (ALIVE) study, a community-recruited observational study of former and current injection drug users (IDUs) with or at high risk for HIV infection in Baltimore, MD. The study included 1178 participants in total with 316 HIV-infected (HV+) and 862 HIV-uninfected (HIV-) IDUs. Multivariate regression analyses were employed, adjusting for age, sex, BMI, smoking, hepatitis C virus co-infection, injection drug use, comorbidities, and HIV status (for all participants), and HIV viral load, CD4+ T-cell counts, and anti-retroviral therapy (for HIV+ participants). The results showed significant impact of aging on all five biomediators and that of HIV infection on all but sTNFR-1. In the adjusted model, neopterin had positive associations with sTNFR-1 and sTNFR-2 (partial correlation coefficients: 0.269 and 0.422 respectively for all participants; 0.292 and 0.354 for HIV+; and 0.262 and 0.435 for HIV-, all p< .0001). No significant associations between neopterin and IL-6 or CRP were identified. Such differential relationships between circulating neopterin and sTNFR-1, sTNFR-2, IL-6, and CRP may help inform their selection in future studies. These findings may also facilitate elucidation of underlying inflammatory and immune activation pathways that contribute to age-related chronic conditions, potentially leading to identification of key biomediators, particularly those upstream of CRP, as novel targets for intervention.